Existence of Solutions for a Class of Coupled Fractional Differential Systems with Nonlocal Boundary Conditions - Tingting Qi; Yansheng Liu; Yujun Cui (Journal of Function Spaces)
Applying Schauder fixed point theorem and Leray-Schauder nonlinear alternative theory, this paper is concerned with the existence of solutions to coupled fractional differential systems with fractional integral boundary value conditions. Meanwhile, two examples are worked out to illustrate the application of the main results.